2020
DOI: 10.2147/ndt.s227598
|View full text |Cite
|
Sign up to set email alerts
|

<p>A Study of Antidepressant Effect and Mechanism on Intranasal Delivery of BDNF-HA2TAT/AAV to Rats with Post-Stroke Depression</p>

Abstract: Post-stroke depression (PSD) is one of the most frequent neuropsychiatric disorders associated with stroke characterized by depression. The neuroplasticity hypothesis postulates that loss of brain-derived neurotrophic factor (BDNF) plays a major role in pathophysiology of PSD, and restoration of it may represent a critical mechanism underlying antidepressant efficacy. Methods: In previous studies, we designed a new fusion gene, HA2TAT-BDNF, and cloned it into adenovirus associated virus (AAV) to construct the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…Although the structural and functional changes implicated in the relationship between depression and neurodegeneration seem to be highly complex, excitingly, several studies have shown altered BDNF production and secretion in a variety of neurodegenerative diseases as well as in depression [ 136 ]. Overall, BDNF is one of the key molecules modulating and linking brain plasticity, and the neuroplasticity hypothesis postulates that the loss of BDNF plays a major role in the pathophysiology of poststroke depression and depression with AD [ 137 , 138 ]. Similarly, in a short review, while providing evidence of shared biological substrates between PD and depression, neuroplasticity was underscored by the roles of BDNF [ 139 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the structural and functional changes implicated in the relationship between depression and neurodegeneration seem to be highly complex, excitingly, several studies have shown altered BDNF production and secretion in a variety of neurodegenerative diseases as well as in depression [ 136 ]. Overall, BDNF is one of the key molecules modulating and linking brain plasticity, and the neuroplasticity hypothesis postulates that the loss of BDNF plays a major role in the pathophysiology of poststroke depression and depression with AD [ 137 , 138 ]. Similarly, in a short review, while providing evidence of shared biological substrates between PD and depression, neuroplasticity was underscored by the roles of BDNF [ 139 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intranasal delivery of an AAV2 construct expressing BDNF fused with cell-penetrating peptides TAT and HA2 to a rat model of poststroke depression reversed the basal decreased sucrose consumption and prolonged immobility in the forced swimming test ( C. Chen et al, 2020 ).…”
Section: Innovation In Nucleic Acid–based Therapeutics Chemistrymentioning
confidence: 99%
“…The authors declare no conflict of interest. Alter inflammatory pathways Improved memory [39,42] ↓ astrocyte/microglia activation [40,41] Improves neuroinflammation Improved memory [46] Traumatic brain injury ↓ lesion volume; ↓ microglia activation [47] FGF Alzheimer's disease ↑ neurogenesis; ↓ hippocampal loss Improved memory [49,50] ↓ Aβ deposition, tau hyperphosphorylation, astrocyte/microglia activation Improved memory [59] Neuroinflammation modifies microglia signaling, DAMPs, PAMPs [51] Parkinson's disease ↑ dopaminergic neuron function; ↓ astrocyte/microglia activation Improves behavioral deficit [53] Stroke (hypoxia/ischemia) ↓ pro-inflammatory cytokines [59] BDNF Depression Improved behavior [63] Parkinson's disease ↑ dopaminergic neurons Improved motor function [68] Stroke No change in infarct volume; altered neuroinflammatory profile [79] NGF Human GBS meningitis* Improved neurological impairment [83] Human traumatic brain injury* ↑ neurogenesis Improved neurological impairment [86] Traumatic brain injury ↓ edema and cell death [82] PACAP Alzheimer's disease ↓ RAGE Improved memory [26,88] Huntington's disease ↑ BDNF, synapses;↓ mutant huntingtin aggregates Improved memory [90] Muscular dystrophy (SBMA) ↑ polyQ-AR degradation; improve neurotoxicity [89] MSC-oligodendrocytes Multiple sclerosis (EAE) ↓ neuroinflammation; ↑ myelination Improved behavior [186] IGF-1, insulin-like growth factor-1; FGF, fibroblast growth factor; BDNF, brain-derived neurotrophic factor; NGF, nerve growth factor; PACAP, pituitary adenylate-cyclase-activating polypeptide 38; GBS, group B Streptococcus; SBMA, spinobulbar muscular atrophy; EAE, experimental autoimmune encephalomyelitis; NBP, DL-3-n-butylphthalide; TGF, transforming growth factor; G-CSF, granulocyte-colony stimulating factor; IL, interleukin; TNF, tumor necrosis factor; MSC, mesenchymal stem cell; EV, extracellular vesicle; PMN, polymorphonuclear neutrophils; DAMP, damage-associated molecular pattern; PAMP, pathogen-associated molecular pattern; RAGE, receptor for advanced glycation end products; polyQ-AR, polyglutamine androgen receptor; BBB, blood-brain barrier; Aβ, amyloid beta; P-gp, p-glycoprotein; VEGF, vascular endothelial growth factor; eNOS, endothelial nitric oxide synthase; Ido-1, indoleamine 2,3-dioxygenase; mTORC1, mammalian target of rapamycin complex 1.The effects following intranasal...…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…Transgenic animal models of AD have shown an inverse correlation between BDNF levels and cognitive performance [ 62 ]. Decreased BDNF levels in brain have been associated with clinical depression [ 63 , 64 ], PD [ 65 ], and AD [ 66 ].…”
Section: Growth Factorsmentioning
confidence: 99%
See 1 more Smart Citation